2007
DOI: 10.3390/medicina43020014
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of hysterectomies

Abstract: The objective of this study was to evaluate and compare operative and postoperative results and differences among laparoscopic, vaginal, and abdominal hysterectomies performed at the Department of Obstetrics and Gynecology of Kaunas University of Medicine Hospital. Methods. A retrospective review of medical histories was performed for women who had undergone three different types of hysterectomies (laparoscopic, vaginal, and abdominal) at the Department of Obstetrics and Gynecology of Kaunas University of Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…But Aniuliene R, et al stated that the difference in mean length of hospital stay was insignificant comparing laparoscopic and vaginal hysterectomies (P>0.05). 7 There were no major complications during the operative procedures in our intervention which is consistent with the findings of Walsh CA, et al 10 25 patients were taken in each arm for the present study. This is consistent with the prevalence of benign diseases of uterus in our institution and the study period of 1 year.…”
Section: Post-operative Complicationssupporting
confidence: 89%
See 1 more Smart Citation
“…But Aniuliene R, et al stated that the difference in mean length of hospital stay was insignificant comparing laparoscopic and vaginal hysterectomies (P>0.05). 7 There were no major complications during the operative procedures in our intervention which is consistent with the findings of Walsh CA, et al 10 25 patients were taken in each arm for the present study. This is consistent with the prevalence of benign diseases of uterus in our institution and the study period of 1 year.…”
Section: Post-operative Complicationssupporting
confidence: 89%
“…In Table 5, the post-operative complication is slightly more in case of NDVH than in TLH. [6][7][8][9] Between TLH and NDVH, we found TLH has a higher mean operating time (99.24min) compared to NDVH (94.76min). But the p value for comparison of this parameter is 0.0915 which is not statistically significant.…”
Section: Post-operative Complicationsmentioning
confidence: 85%
“…14 Chen B et al reported significantly less blood loss in vaginal group (mean 30.4 ml) compared to abdominal group (mean 70.3 ml). 13 The average blood loss in TAH group in our study was 80 ml more than the NDVH group.…”
Section: Resultsmentioning
confidence: 99%
“…The quoted blood loss figures in the literature show that laparoscopic surgery definitely is beneficial in terms of blood loss as compared to abdominal surgery. 21 The reason probably is the use of diathermy as the main modality for pedicles which reduces the blood loss.…”
Section: Discussionmentioning
confidence: 99%